(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Creativity is considered a very complex phenomenon. Some writers have defined creativity as process while other specifies it as a product. Some specify that creativity contributions must be true, generalizable and surprising in view of what existed at the time of the discovery. Some scholar insist that the term, creative be reserved for some very rare and particular kind of ability, while others apply the term to a general creative ability possessed to some degree by all essentially healthy individuals. Creativity is a mental process involving the generation of new ideas or concepts or new associations between existing ideas or concepts.